2010
DOI: 10.1099/mic.0.039867-0
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni 81-176 forms distinct microcolonies on in vitro-infected human small intestinal tissue prior to biofilm formation

Abstract: Human small and large intestinal tissue was used to study the interaction of Campylobacter jejuni with its target tissue. The strain used for the study was 81-176 (+pVir). Tissue was processed for scanning and transmission electron microscopy, and by immunohistochemistry for light microscopy. Organisms adhered to the apical surface of ileal tissues at all time points in large numbers, in areas where mucus was present and in distinct groups. Microcolony formation was evident at 1–2 h, with bacteria adhering to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…6 ). This is consistent with two previous studies have noted that bacteria adhere to ex vivo tissue samples by flagella in microcolony-like structures [27], [29]. Analysis of biofilm formation on abiotic surfaces also found microcolonies formed on glass coverslips with flagella forming bridges between organisms [30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6 ). This is consistent with two previous studies have noted that bacteria adhere to ex vivo tissue samples by flagella in microcolony-like structures [27], [29]. Analysis of biofilm formation on abiotic surfaces also found microcolonies formed on glass coverslips with flagella forming bridges between organisms [30].…”
Section: Discussionsupporting
confidence: 92%
“…Molecular factors that mediate C. jejuni biofilm formation are also poorly understood. Flagella are required [17], [25], [26] and may mediate adhesion - both bacteria-bacteria and biofilm-host cell [27][29]. Whether motility or the flagellar structure itself is important, and at which stage each is required, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…First, flagellum-driven motility enables C. jejuni to travel through and colonize the highly viscous mucus layer covering the surface of epithelial cells (6,7). Second, the flagellum filament is an adhesin that promotes contact to host cells and contributes to bacterial binding of the host epithelium (8)(9)(10). Likewise, C. jejuni motility is necessary for maximal invasion of human intestinal epithelial cells in vitro (11).…”
mentioning
confidence: 99%
“…Based on the results of the ciprofloxacin susceptibility test, however, biofilm did not make differences in the emergence of FQ R exceeding the breakpoint MIC of ciprofloxacin (4 g ml Ϫ1 ) suggested by the Clinical and Laboratory Standards Institute (CLSI) (9), compared to planktonic cells (data not shown). C. jejuni's ability to form biofilms is important for human infection and survival in harsh environments (10,11). Interestingly, it has been reported that high numbers of Campylobacter spp.…”
mentioning
confidence: 99%